Expanding the Ultracompacts: Gravitational-wave-driven Mass Transfer in the Shortest-period Binaries with Accretion Disks - Joheen Chakraborty; Kevin B. Burdge; Saul A. Rappaport; James Munday; Hai-Liang Chen; Pablo Rodríguez-Gil; V. S. Dhillon; Scott A. Hughes; Gijs Nelemans; Erin Kara; Eric C. Bellm; Alex J. Brown; et al. (The Astrophysical Journal)
We report the discovery of three ultracompact binary white dwarf systems hosting accretion disks, with orbital periods of 7.95, 8.68, and 13.15 minutes. This significantly augments the population of mass-transferring binaries at the shortest periods, and provides the first evidence that accretors in ultracompacts can be dense enough to host accretion disks even below 10 minutes (where previously only direct-impact accretors were known). In the two shortest-period systems, we measured changes in the orbital periods driven by the combined effect of gravitational-wave emission and mass transfer. We find $\dot{P}$ is negative in one case, and positive in the other. This is only the second system measured with a positive $\dot{P}$ , and it is the most compact binary known that has survived a period minimum. Using these systems as examples, we show how the measurement of $\dot{P}$ is a powerful tool in constraining the physical properties of binaries, e.g., the mass and mass–radius relation of the donor stars. We find that the chirp masses of ultracompact binaries at these periods seem to cluster around ${{ \mathcal M }}_{c}\sim 0.3M_{\odot }$ , perhaps suggesting a common origin for these systems or a selection bias in electromagnetic discoveries. Our new systems are among the highest-amplitude known gravitational-wave sources in the millihertz regime, providing an exquisite opportunity for multimessenger study with future space-based observatories such as LISA and TianQin. We discuss how such systems provide fascinating laboratories to study the unique regime where the accretion process is mediated by gravitational waves.